Foliar application of water soluble fertilizers in summer groundnut in a Vertisols: Foliar application of water soluble fertilizers in summer groundnut in a Vertisols - B S YEANGI; ROOPA; U IRAMMA GOUDAR; P NAGARAJU (Journal of Oilseeds Research, 2020)
A field experiment was carried out during summer season to know the effect of water soluble fertilizers on the performance of groundnut (cv. TAG 24) in Vertisols of Northern Transition Zone of Karnataka. Application of FYM + 100% RDF + foliar spray of fertilizers at 30, 45 and 60 days after sowing (DAS) recorded 7.35% higher pod yield over application of 100% RDF and was on par with the treatment receiving FYM + 85 % RDF + foliar spray of fertilizers at 30, 45 and 60 DAS and recorded the highest B:C ratio.